Association of socio-demographic issues with level of knowledge of HIV/AIDS among injecting drug users in Dhaka City in Bangladesh (South East Asia Journal of Public Health, 2017)
Human Immune Deficiency Virus (HIV) and Acquired immune Deficiency Syndromes (AIDS) continues to be a major burden of morbidity and mortality among the population. Injecting drug users (IDUs) are at high risk of contracting the disease. The study was conducted to assess the level of knowledge of HIV/AIDS and the influence of different socio-demographic factors among IDUs in Dhaka city, Bangladesh. A descriptive type of cross-sectional study was conducted. A total of 200 injecting drug users were selected purposively. A semi-structured questionnaire was used for collecting socio-demographic information of the respondents and their knowledge regarding HIV/AIDS. The level of knowledge was categorized into two: poor (